AN ANALYSIS OF PARAPHRASING TECHNIQUE USED BY STUDENT OF ENGLISH DEPARTMENT - Lia, Agnes Mejika April; Angraini, Nike; Anggraini, Dita Rizki (JURNAL ILMIAH EDUNOMIKA, 2024)
Paraphrasing is an important technique in academic writing to avoid plagiarism,understanding the material and convey information in your own language. This research examines the paraphrasing methods employed by English study program students at Indo Global Mandiri University in Palembang using qualitative research, specifically thematic analysis, and data collection techniques including tests and interviews. The study involved 8 out of 16 eighth-semester students. For the test, the participants paraphrased a descriptive text provided by the researcher, and the interview comprised 8 questions related to paraphrasing. The findings revealed that most techniques used by students were changing vocabulary and the obstacles when paraphrasing texts were lack of vocabulary and poor/lack of documentation skills. Moreover, the research found that the conditions for students to use paraphrasing were to avoid plagiarism, avoid direct quotations in writing, increase the clarity of writing, and complete writing assignments during class.